The ecological domain in the sustainability science research and education - Jarzebski, Marcin Pawel; Kudo, Shogo (Ecological Questions, 2017)
A single disciplinary approach fails to tackle problems threatening the sustainable development. Thus, the sustainability science – focused on the problem, normative, and covering many disciplines – has been developed and recognized as critical in creating solutions that could actually trigger a global change. As an example, environmental issues are no longer the problem to be solved within the ecological domain but the primary and complex sources of the problem must be analysed from the social, economic and technical perspectives as well, using methodological tools allowing for a variety of disciplines. This study provides a systematic review of publications related to sustainability and ecology, and briefly explains the role of environmental knowledge in the sustainability education. The study has shown that despite a common scepticism about combining qualitative and quantitative approaches the employment of miscellaneous disciplines has become a common approach and ecology in the context of sustainability goes beyond the ecological research. It appears from the reviewed curriculum of the sustainability science graduate programme at the University of Tokyo that environmental knowledge is well established, but is generally driven by transdisciplinary courses. It was included in the half of credits from compulsory courses, whereas elective courses are those which are open to other disciplines.